Mindfulness and the cultural psychology of personhood: Challenges of self, other, and moral orientation in Haiti. (September 2019) - Hoffman, Diane M
The global spread of mindfulness-based interventions raises some interesting questions regarding the universality and translatibility of key ideas and practices of mindfulness. Based on ethnographic research, this article reflects on one effort to bring ideas and practices of mindfulness-based stress reduction to Haitian mental health practitioners and educators in Haiti. While core concepts of mindfulness-based stress reduction are often assumed to be universal, this analysis suggests that cultural meaning systems and social contexts, and in particular local cultural psychologies of personhood, strongly influenced the meanings that Haitian participants took away from their exposure to mindfulness-based stress reduction. These differences manifested in resistance to individualist concepts self-embedded in the discourse of mindfulness-based stress reduction as well as to its secularism. However, while rejecting an individualistic and amoral self-focus, Haitian participants also re-interpreted mindfulness in new ways that stressed its value for societal and national well-being. The article reflects on the larger questions that surround the making and re-making of meanings associated with well-being as mindfulness-based interventions move across cultural and national borders.